Political Trends Affecting Nonmetropolitan America - Paul M. Nachtigal (Journal of Research in Rural Education, 1994)
There are two stories concerning political trends affecting nonmetropolitan America that I would like us to examine. There is the old story that has had afairly straightforward,jairly predictable, andfor rural America afairly discouraging story line. It is a story of declining rural population, a declining influence in the creation of public policy, and as a consequence, irrelevant education in rural communities. It is a story that has its roots in the very early deliberations ofhow this country would govern itself. It is a story ofdiffering philosophical beliefs about how individuals live together. It is ultimately a story that pits urban interests against rural interests. And, because ofthe way the rules ofthe game have been established, the interests that get served are those ofthe political victors.